REPRESENTASI FEMINISME DAN MASKULINISME DALAM NOVEL TUHAN IJINKAN AKU MENJADI PELACUR KARYA MUHIDIN M. DAHLAN - Arif Viani, Mahcmuddah; Nugroho, Wahyu Budi; Punia, I Nengah (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT The results of the novel discourse analysis are in the subject's position, Kiran is placed in a position that using men in retaliation for his disappointment with God, rejecting the concept of marriage. At the position of the object, Kiran was shown as the sexual object. In the position of the author, Muhidin uses a single first person pronoun to describe the Kiran’s figure in a more dominating subject position. In the position of the writer, Kiran is more to the position of the subject related to her actions which try to rebel from the social order which is considered to have restrained her. The representation of feminism and masculinity in terms of theory of gender performativity and deconstruction theory, Kiran’s figure are a resistance as well as a critique of law and social values which he considers impartial to women and community stigma related to gender-based actions. Keywords; Feminist Discourse Analysis, Kiran, Gender Performativity, Deconstruction ABSTRACT The results of the novel discourse analysis are in the subject's position, Kiran is placed in a position that using men in retaliation for his disappointment with God, rejecting the concept of marriage. At the position of the object, Kiran was shown as the sexual object. In the position of the author, Muhidin uses a single first person pronoun to describe the Kiran’s figure in a more dominating subject position. In the position of the writer, Kiran is more to the position of the subject related to her actions which try to rebel from the social order which is considered to have restrained her. The representation of feminism and masculinity in terms of theory of gender performativity and deconstruction theory, Kiran’s figure are a resistance as well as a critique of law and social values which he considers impartial to women and community stigma related to gender-based actions. Keywords; Feminist Discourse Analysis, Kiran, Gender Performativity, Deconstruction